2023
DOI: 10.1038/s41698-023-00374-z
|View full text |Cite
|
Sign up to set email alerts
|

Prediction model for drug response of acute myeloid leukemia patients

Abstract: Despite some encouraging successes, predicting the therapy response of acute myeloid leukemia (AML) patients remains highly challenging due to tumor heterogeneity. Here we aim to develop and validate MDREAM, a robust ensemble-based prediction model for drug response in AML based on an integration of omics data, including mutations and gene expression, and large-scale drug testing. Briefly, MDREAM is first trained in the BeatAML cohort (n = 278), and then validated in the BeatAML (n = 183) and two external coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
2
1
0
Order By: Relevance
“…For model building, we utilized all available data types, namely clinical, RNA, and Whole Exome sequencing, in isolation and all possible combinations. Our analysis showed similar overall performance compared to previous efforts [5]. Specifically, Quang et al [5] used a single hold-out approach to evaluate performance and reported a median correlation of 0.35.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…For model building, we utilized all available data types, namely clinical, RNA, and Whole Exome sequencing, in isolation and all possible combinations. Our analysis showed similar overall performance compared to previous efforts [5]. Specifically, Quang et al [5] used a single hold-out approach to evaluate performance and reported a median correlation of 0.35.…”
Section: Discussionsupporting
confidence: 78%
“…Our analysis showed similar overall performance compared to previous efforts [5]. Specifically, Quang et al [5] used a single hold-out approach to evaluate performance and reported a median correlation of 0.35. Even though they used information from the Whole Exome and RNA sequencing data, they utilized only the RNA sequencing as input in the training process.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation